Model of Advocacy Coalitions in the Formulation of Spatial Plan Policy of Makassar in 2010-2030 - Prianto, Andi Luhur (BISNIS & BIROKRASI: Jurnal Ilmu Administrasi dan Organisasi, 2014)
Policy formulation is laden with conflicts. Many actors can be involved in conflict and they form advocacy coalitions. This study aims to analyze the role of internal parameters and external system events of coalition in the formulation of spatial plan policy of Makassar, belief systems of the coalition actors in the process of policy formulation, and interaction between policy subsystems in the process of policy formulation. The research was conducted at several institutions related to the formulation of spatial plan policy of Makassar. This research is a qualitative research and data were collected through library and field study by employing observations and interviews which are analyzed by interactive model. The results showed that there are two influential internal parameters; technocratic approach and the weakness of legislation capacity in Makassar Council. Meanwhile, external system events of coalition came from the political situation of South Sulawesi governor election, and the release of Presidential Decree Number 122 of 2012 about reclamation of coastal regions and small islands. Belief system of coalitions in characterized by differences in the characteristics of actors from various institutions, which affect the response of actors that make up coalition formation. Policy subsystems lead to the formation of advocacy coalition (support the legalization, against the legalization, and policy brokers).